Dry hot air reduces seedborne pathogens of carrot seeds - Cheah, L-H.; Townshend, J.; Hedderley, D.I. (New Zealand Plant Protection, 2010)
The effect of dry hot treatment of carrot seeds on seedborne pathogens (Alternaria dauci Fusarium solani and Xanthomonas sp) and seed germination was investigated Carrot seeds (no fungicide) were soaked in water for 1 min before being exposed to hot air (70C or 75C) for 10 20 or 30 min and then plated on potato dextrose agar to assess pathogen growth Treated seeds were sown in cell trays in a glasshouse to assess germination and weight of subsequent seedlings All dry hot air treatments significantly (P